A Study of Professionalism of Secondary School Teachers with respect to Education Board - Varia, Vishal (IJRDO- Journal of Educational Research, 2016)
Professionalism has always been in the area of interest for people. It deals with the art of being perfect inyour area of work. Professionalism means to be complete in oneself and that one is not required to be reminded ofduties and responsibilities. Considering teaching as profession has always been a hot topic. There is a school ofthought that opines for the teaching as a profession as it requires necessary hard work, skills and qualification alongwith training and internship, where as the other school of thought opines against teaching as a profession as it doesnot include any official ceremony for awarding professional qualification and that there is no single organizationwhere the teachers are registered as a professional. As such there are many view points of this. The present researchjust focuses on the professionalism of a Gujarat Board teacher as compared to Other Board teacher.The study was conducted on 1044 teachers of secondary schools in Saurashtra Region Comprising of 11districts of Gujarat. The study was conducted using a self constructed scale “Secondary School TeachersProfessionalism Scale”. The variable under study was Education Board. The method of research was descriptivesurvey research. The tool comprised of ten components viz. Time Keeping, Content Mastery, ContemporaryKnowledge, Communication with Students, Communication with Colleagues, Delivery Mechanism, Pro-Activenessand Follow up, Parents Counselling and Students Counselling.The findings of the research are that as far as Education Board is Concerned, the Other Board Teacherswere found to be better than Gujarat Board Teachers for Time Keeping, Content Mastery, ContemporaryKnowledge, Delivery Mechanism, Parents Counselling and Students Counselling. Whereas the Gujarat Boardteachers were found to be better than Other Board teachers for Communication with Students and Pro Activness andFollowups. However, there was no considerable difference between the two for Physical Appearance andCommunication With Colleagues. Schools and Educational institutes can use the tool to measure the professionalism of teachers and candevice training programmes to enhance professionalism for relevant components. Over all, the research will help theteacher in general to measure the professionalism of self and motivate development of professionalism.